High Dispersivity Bacterial Cellulose/Carbon Nanotube Nanocomposite for Sensor Applications - Olyveira, Gabriel Molina [UNESP]; Manzine Costa, Ligia Maria; Basmaji, Pierre (Amer Scientific Publishers, 2013)
Bacterial cellulose (BC) has established to be a remarkably versatile biomaterial and can be used in wide variety of applied scientific endeavors, especially for medical devices. In fact, biomedical devices recently have gained a significant amount of attention because of increased interesting tissue-engineered products for both wound care and the regeneration of damaged or diseased organs. The architecture of BC materials can be engineered over length scales ranging from nano to macro by controlling the biofabrication process, besides, surface modifications bring a vital role in in vivo performance of biomaterials. In this work, bacterial cellulose fermentation was modified with carbon nanotubes for sensor applications and diseases diagnostic. SEM images showed that polymer modified-carbon nanotube (PVOH-carbon nanotube) produced well dispersed system and without agglomeration. Influences of carbon nanotube in bacterial cellulose were analyzed by FTIR. TGA showed higher thermal properties of developed bionanocomposites.
Keywords: Bacterial Cellulose (Nanoskin); Carbon Nanotubes; Biocomposites; Sensor Applications